2013
DOI: 10.1017/s143192761300010x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Investigations of Streak Formation in 6063 Aluminum Extrusions by Optical Metallographic Techniques

Abstract: The present study investigates the effect of the solidification strategy for AA 6063 alloy on the surface appearance of anodized extrusions. The microstructure of the samples was analyzed using both light optical microscopy and scanning electron microscopy. Results show that if heavy segregation occurs from rapid solidification, coarse Mg2Si particles form, thus reducing the potential for precipitation strengthening by the finer β-Mg2Si developed in the solid state. Differentially-strained regions formed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The Mg2Si and FeAlSi could be identified from the black and white colors, respectively. This finding was similar to the study by Voort et al, [20]. The AR sample consists of coarse Mg 2 Si and FeAlSi while the NT and TT500 consist of mixed coarse and fine Mg 2 Si and FeAlSi.…”
Section: Resultssupporting
confidence: 92%
“…The Mg2Si and FeAlSi could be identified from the black and white colors, respectively. This finding was similar to the study by Voort et al, [20]. The AR sample consists of coarse Mg 2 Si and FeAlSi while the NT and TT500 consist of mixed coarse and fine Mg 2 Si and FeAlSi.…”
Section: Resultssupporting
confidence: 92%
“…Overall, all the extrudates exhibited the presence of Mg2Si and spheroidal Al-Fe-Si rich precipitates, which could be identified from the black spot and light grey, respectively. This result was similar to the finding in the study by Voort et al [27]. The extrudate of solid as-received consist of coarse Mg2Si and AlFeSi precipitate, while the chip-based extrudates of untreated and thermally-treated showed fine precipitate.…”
Section: Resultssupporting
confidence: 91%
“…Gjonnes et al [22] attributed the formation of shingles on rolled Al alloys due to local adhesion and sticking, followed by deformation and rupture of the metal surface after passing through the deformation rolls. Vander voort et al [30] showed that the difference in local number density of second phases or intermetallics on the Al surface causes local differences in temperature rise, and extent of deformation under rolling and thus leads to a heterogeneity in surface roughness causing streaks on the rolled Al surface. In general the defects on rolled Al alloys are reported to be formed mainly due to the presence of intermetallic phase particles that interact with the roll counter face and modify the local microstructure, texture and morphology of the Al metal under high shear forces [31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%